Carrier-envelope phase stabilized 5.6fs, 1.2mJ pulses - Mashiko, Hiroki; Nakamura, Christopher M.; Li, Chengquan; Moon, Eric; Wang, He; Tackett, Jason; Chang, Zenghu (My University, 2007)
The authors report the generation of 1.2mJ pulses with a duration of 5.6fs from a neon filled hollow-core fiber seeded with carrier-envelope phase stabilized 2.2mJ, 25fs pulses. The carrier-envelope phase after the fiber was measured by a second, out-loop f-to-2f interferometer. With seed pulse power locked, the carrier-envelope phase of the two-cycle pulses is controlled to a standard deviation of 370mrad. The peak power of the carrier-envelope phase stabilized pulses, 0.2TW, is twice that previously generated. The significance of seed pulse energy stability for carrier-envelope phase stabilization of few-cycle laser pulses is demonstrated.